Política pública de regularização fundiária urbana: estudo de legislação dos munícipios da região Sudoeste do Paraná - Pimentel, Franciane de Souza Andreghetto (2025)
The study of land regularization is extremely important in the context of regional development and in the field of public policies. With the formation of informal urban centers due to the growing process of urbanization, it has become a priority to study effective public policies that are clear and specific, and integrate the principles of social inclusion, legality, and environmental sustainability. Thus, this research analyzed the effectiveness of urban land legislation in the municipalities of the Southwest Region of Paraná, based on Law No. 13,465, of July 11, 2017. It also addressed how this public policy of land regularization was implemented in each municipality studied. The aim was to contextualize public policies related to urban land regularization based on federal legislation and how they can be designed at the municipal level, in addition to analyzing the public policy of urban land regularization through the legislation of the municipalities of Southwest Paraná, as well as identifying whether the legislation of urban land regularization of the municipalities of the Southwest Paraná Mesoregion met the environmental, legal, urban and social aspects of this public policy. The importance of this research for other municipalities is significant, as it offers analytical, legal and technical subsidies that can be used to improve or review municipal legislation on urban land regularization, especially small and medium-sized municipalities, which are common in the Southwest Paraná Mesoregion, also serving as a basis for new academic work, in addition to contributing to urban planning strategies, master plans and housing policies in different municipal contexts. The methodology of the work was documentary and descriptive research, where the municipal legislation of each of the seven municipalities was studied, in addition to the federal legislation on the subject. In order to achieve the proposed objectives, it was first necessary to delimit the research site, where in the first phase an exploratory research was carried out in the 42 municipalities that make up the Southwest region of Paraná, of which seven municipalities were delimited where the research was carried out, as they have urban land regularization in accordance with Law No. 13,465/2017. The results showed that, in relation to the environmental, social, legal and urban aspects of each municipal legislation, it is possible to affirm that the laws analyzed are moving towards seeking the realization of the social function of property, and that the effectiveness and degree of detail of each of the municipal laws are in accordance with the political and technical capacity of each location. The legislations show important advances, but also demonstrate the differences in the structure of each legislation, regarding the aspects studied, as well as the planning capacity of each location. Urban land regularization is an essentially interdisciplinary and multidimensional process, as it articulates different spheres of public power action and different fields of knowledge. It requires not only the existence of legal instruments, but also a sufficient and efficient technical structure, political will integrated with public policies that aim at social justice, urban planning, housing, the environment and an articulated social response, focused on dignity and the right to the city.